2015
DOI: 10.1016/j.ntt.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and behavioral consequences of prenatal methamphetamine exposure: A review of the Infant Development, Environment, and Lifestyle (IDEAL) study

Abstract: This study reviews the findings from the Infant Development, Environment, and Lifestyle Study (IDEAL), a multisite, longitudinal, prospective study designed to determine maternal outcome and child growth and developmental findings following prenatal methamphetamine exposure from birth up to age 7.5 years. These findings are presented in the context of the home environment and caregiver characteristics to determine how the drug and the environment interact to affect the outcome of these children. No neonatal ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 64 publications
6
48
1
2
Order By: Relevance
“…The normal physical examination and normal-appearing brain magnetic resonance imaging are consistent with results from the multicenter Infant Development, Environment, and Lifestyle (IDEAL) study, which found no increased incidence of congenital abnormalities 54 or abnormal head sonograms 55 in infants with prenatal methamphetamine exposure. However, on neurologic evaluation, our methamphetamine/tobacco group had delayed development on active muscle tone and total ATNAT scores, although these scores appeared to normalize at 3 to 4 months of age.…”
Section: Discussionsupporting
confidence: 81%
“…The normal physical examination and normal-appearing brain magnetic resonance imaging are consistent with results from the multicenter Infant Development, Environment, and Lifestyle (IDEAL) study, which found no increased incidence of congenital abnormalities 54 or abnormal head sonograms 55 in infants with prenatal methamphetamine exposure. However, on neurologic evaluation, our methamphetamine/tobacco group had delayed development on active muscle tone and total ATNAT scores, although these scores appeared to normalize at 3 to 4 months of age.…”
Section: Discussionsupporting
confidence: 81%
“…Although there are no comparable human studies of MDMA exposure, after prenatal exposure to methamphetamine, a similar amphetamine type drug, Smith et al (Smith LM et al, 2015) found that methamphetamine-exposed infants demonstrated motor deficits relative to comparison infants. Specifically, they identified poorer quality of movement in the neonatal period, and decreased grasping skill with heavier exposure at 1 and 3 years (Smith LM et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they identified poorer quality of movement in the neonatal period, and decreased grasping skill with heavier exposure at 1 and 3 years (Smith LM et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…MA is a potent psychostimulant that blocks DA reuptake (Sulzer et al 2005). Children exposed to intrauterine MA show changes in cellular metabolism in the striatum and frontal lobe (Smith et al 2001; Chang et al 2009) and significant volume reductions in the putamen, caudate nucleus, globus pallidus, and hippocampus (Derauf et al 2009; Smith et al 2015) that correlate with attention, verbal memory, and reaction time deficits (Chang et al 2004). Nearly half (42 %) of women who reported MA use during pregnancy continued using during the third trimester (Della Grotta et al 2010).…”
Section: Introductionmentioning
confidence: 99%